Scientific study on the indigenous technology of Dahi making of eastern Nepal - Bhattarai, Rewati Raman; Das, Suman Kumar Lal (2013)
Dahi is the traditional fermented milk product indigenous to Nepal having its history dating back to ancient times. The preparation method is unique with steps like saans marne, naato banne and uses special close necked wooden vessel carved out of wood called theki for fermentation. Caramelization during heating and duration of fermentation affects color, appearance and form of dahi. The best flavor comes from dahi prepared in daar theki. Heat treatment affects microstructure, texture and rheology of dahi. A good dahi should possess firm body, consistent quality with equal ration of sweetness and sourness. Dahi is indispensible item in Nepalese religious and cultural occasions which is nutritionally and therapeutically superior to milk. Storage life of dahi can be extended by a semi-continuous mode.